The Correlation Between Advertisements Of Badan Amil Zakat And The Intention Of Muslim Community In Performing Zakat Obligation - Lestari, Diana; Kusumawati, Dea; Panorama, Maya (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Zakat is one of the obligatory acts of worship for every Muslim, therefore the understanding of zakat needs to be continuously disseminated to the Muslim community in various ways. Comprehensive Islamic learning needs to be emphasized in order to be able to instill values ​​about the importance of zakat, through formal and non-formal education, socialization about zakat should be held. There is an institution that is mandated to manage zakat, which is known as the amil zakat agency. The role of amil zakat should be central in society to teach zakat, one of which is through advertising in the media. This study was conducted to determine the correlation of the implementation of the Amil Zakat Agency advertisement with the public's intention to pay zakat. The research implementation refers to quantitative descriptive research methods, through data collected from research questionnaires and documentation. The data obtained were analyzed through a quantitative test with the Pearson Correlation test. The results obtained from this study are that advertisements organized by the Amil Zakat Agency have a positive and significant correlation with people's intentions to pay zakat. This is based on the test results which show the rcount value of 0.901 > rtable 0.3610 so that the alternative hypothesis statement is accepted and the null hypothesis or statistical hypothesis is rejected. Keywords: Advertisement, Zakat Agency, Intention To Pay